Perancangan Sistem Informasi Tracking Proses Di Departemen Pengadaan Jasa Pada PT Pupuk Sriwidjaja Palembang - Sri Jayanti; M. Syendi Apriko (CV. Multi Kreasi Media, 2025)
The service procurement process at PT Pupuk Sriwidjaja Palembang is still carried out manually, causing various obstacles, such as delays in information, difficulties in tracking documents, and a lack of transparency between departments. To overcome these problems, a web-based process tracking information system was designed with the aim of improving efficiency, transparency, and accuracy in service procurement data management. This study used the Rapid Application Development (RAD) method, which consists of four stages: requirements planning, user design, construction, and implementation. The design resulted in a system prototype with key features such as a dashboard, procurement data, process tracking, documents, reports, user management, and notifications. This system enables real-time monitoring of procurement status, speeds up communication between departments, and facilitates the preparation of digital reports. With this information system, the service procurement process at the Service Procurement Department of PT Pupuk Sriwidjaja Palembang has become more integrated, efficient, and accountable.